Lampião da esquina: lutas feministas nas páginas do "Jornal Gay", luzes em tempos sombrios (Brasil, 1978-1981) - Silva, Daniel Henrique de Oliveira (2016)
What are the feminine representations built and disseminated in the pages of a newspaper written by gay editors? This question directs research that seeks to understand how gay men, inferior and stigmatized socially subject, gave visibility to another marginalized group, in this case women, the pages of a considered marginal newspaper, the lantern corner, which appeared in 1978, the final years civil dictatorship - military. in this research, we sought to contextualize its appearance and dialogue with other movements, trying to understand this relationship with the feminist movements of the final years of civil dictatorship - military, through the stories published over the pages of the newspaper.